2019
DOI: 10.1080/15548627.2019.1569929
|View full text |Cite
|
Sign up to set email alerts
|

Gyp1 has a dual function as Ypt1 GAP and interaction partner of Atg8 in selective autophagy

Abstract: Macroautophagy/autophagy is a highly conserved intracellular vesicle transport pathway that prevents accumulation of harmful materials within cells. The dynamic assembly and disassembly of the different autophagic protein complexes at the so-called phagophore assembly site (PAS) is strictly regulated. Rab GTPases are major regulators of cellular vesicle trafficking, and the Rab GTPase Ypt1 and its GEF TRAPPIII have been implicated in autophagy. We show that Gyp1 acts as a Ypt1 GTPase-activating protein (GAP) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Gyp1 has dual functions, as a GAP for Ypt1 and as an interacting partner of Atg8 in selective autophagy ( Mitter et al, 2019 ). For its stability and normal subcellular localization, Gyp1 (a GAP for Ypt1) needs to interact with Ypt32 ( Rivera-Molina and Novick, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gyp1 has dual functions, as a GAP for Ypt1 and as an interacting partner of Atg8 in selective autophagy ( Mitter et al, 2019 ). For its stability and normal subcellular localization, Gyp1 (a GAP for Ypt1) needs to interact with Ypt32 ( Rivera-Molina and Novick, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study suggests that Gyp1, a GAP (GTPase-activating protein) of Ypt1, has been identified as a novel Atg8 interaction partner. Loss of Gyp1, its GAP activity, or its first AIM; AIM1 (160-163 a.a.) causes a partial reduction in mitophagy, yet how Gyp1 contributes to autophagosome formation remains elusive [31].…”
Section: Pink1-mediated Ubiquitin Phosphorylationmentioning
confidence: 99%
“…Gyp1 also plays a role in autophagy. It regulates the disassembly of Ytp1–Atg1 complexes, as well as the interaction of cargo receptor and Atg8 proteins in selective autophagy [ 93 ]. In humans, 38 Rab GAPs have been identified, with TBC1D20 (Gyp8 in yeast) being the specific (but not exclusive) GAP for Rab1.…”
Section: Rab1mentioning
confidence: 99%